Węgrzy w Małopolsce w X-XII wieku w świetle źródeł toponomastycznych i archeologicznych - Florek, Marek (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2023)
This article deals with the interpretation of toponyms and archaeological materials from early medieval Lesser Poland that may be associated with the Hungarians or the Khazar Kabars. So far, they have most often been interpreted as traces of invasions by Hungarians – nomads (single monuments) or the operations of watchtowers they established to control the passes through the Carpathians and subjugated the local Slavic population (the so-called Old Magyar cemetery in Przemyśl) in the late 9th and 1st half of the 10th century. It could have been related to their participation in the armed squads of the Piasts or the Rurikiviks, the activities of Hungarian merchants or prisoner-of-war settlements. The dating and interpreting the so-called Old Magyar cemetery in Przemyśl remains an open issue until it is fully developed and the results published.